Pengaruh Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak di Mediasi Oleh Sistem Pajak Elektronik - Rimbi Rianthi, Gusti Ayu Putu; Alit Erlina Wati, Ni Wayan (Hita Akuntansi dan Keuangan, 2025)
The development of a country's economy depends on an efficient tax structure.  Taxes constitute the primary instrument within Indonesia’s state revenue structure, functioning to fund government expenditures. This research seeks to explore the mediating effect of the computerized tax system in the relationship between tax knowledge and individual taxpayer compliance.  A questionnaire survey of 115 individual taxpayers at KPP Pratama Tabanan was used in this quantitative investigation. By applying SEM-PLS as the analytical method, the study demonstrates that tax knowledge has a favorable effect on taxpayer compliance and promotes the adoption of the electronic tax system, and that the electronic tax system has a favorable effect on compliance.  According to mediation tests, the electronic tax system somewhat mediates the relationship between tax knowledge and compliance.  These findings suggest that increasing tax literacy and utilizing computerized tax systems to their fullest potential are two crucial strategies for improving compliance.